PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI BANGUN RUANG KELAS V SD NEGERI KEDUNGSARI KABUPATEN PURWOREJO - Habib Rohman; Yuli Widiyono; Titi Anjarini (STKIP Subang, 2024)
The objective of this study is to investigate the implementation of the project-based learning (PjBL) model to enhance learning motivation and critical thinking skills on the topic of geometric shapes in Grade V at SD Negeri Kedungsari, Purworejo Regency. This classroom action research was conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects of this study were the teacher and 24 Grade V students, including 14 male and 10 female students. Data collection techniques and instruments included observation, interviews, and tests. Data analysis techniques employed both qualitative and quantitative analysis. The results of this study show that the learning motivation of Grade V students in the geometric shapes topic had an average score of 58.2% in the pre-cycle, 75.1% in the first cycle, and 90.25% in the second cycle. Thus, it can be concluded that the implementation of the PjBL model can increase students' learning motivation. The critical thinking skills of students applying the PjBL model were 64.1% in the pre-cycle, 72.9% in the first cycle, and 86.1% in the second cycle. Therefore, it can be concluded that the implementation of the PjBL model can enhance students' critical thinking skills.